ANALISIS KEDISIPLINAN KINERJA GURU IPA TERPADU SE-KECAMATAN TAMBUSAI TAHUN PEMBELAJARAN 2015/2016 - Ummi, Nurul (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This research aims to the discipline of natural science teacher performance in Tambusai subdistrict. Type Research is descriptive. The population in this research was all of the science teacher in Tambusai subdistrict which was 10 people and 6 headmasters as comparative. Intake of sampel use saturated sampel of its meaning of. Technique determination of sampel if when all population member used as sampel. Technique data collecting use enquette. From result of entirety got percentage of mean 79,52% with good criteria.